Analysis of classical techniques precision on the measurement of cellulose moisture gain/loss - Cichosz, Stefan; Masek, Anna; Dems-Rudnicka, Katarzyna (Frontiers in Chemistry, 2023)
The precision of the four classical techniques (Karl-Fischer titration, (thermo)gravimetric method, Fourier-transform infrared (FT-IR) and near infrared (NIR) spectroscopies) commonly used in the analysis of cellulose moisture absorption/desorption has been deeply investigated regarding the reproducibility of these processes. Based on multiple repeated experiments, cellulose water content values obtained with Karl-Fischer titration and (thermo)gravimetric method were plotted as a function of time. Then, the cautious peak-by-peak analysis of the absorbance and wavenumber shifts visible in IR spectra has been carried out. The collected data was described using boxplots that provided valuable information on the experimental points spread. It has been successfully proven that gravimetric methods allow for precise drawing of moisture absorption and desorption curves, while Karl-Fischer titration, ATR FT-IR and NIR techniques provide the possibility of the moisture absorption/desorption processes description by linear mathematical models (R2>90%). Therefore, this study provides a systematic comparison between various analytical methods.